Petition-and-Response and Liminal Petitioning in Comparative/Historical Perspective. Issue 3 (2019) - Zaret, David
Abstract : Before its deployment as a practice by insurgent social movements for mobilizing public opinion in the long nineteenth century, petitioning was a ubiquitous, relatively uniform practice with no connection to popular insurgency. It was nearly the inverse, though just as prominent, phenomenon: an instrument of state as opposed to an instrument of protest, occurring wherever rulership relied on administrative techniques for generating and deploying its authority. Humble subjects sought benevolent deployments of power in pursuit of goals that were within and not about the rules of the game. This mode of petitioning is aptly described as petition-and-response, a term of art from classical scholarship that is applicable to diverse patrimonial states across Eurasia with diverse ideological systems. The transition to modern petitioning as a repertoire for contentious politics was an extended, uneven process. It was facilitated initially by the unquestioned legitimacy of petitionary etiquette with regard to form and rhetoric, as opposed to explicit invocation of novel ideas about natural rights. Liminal petitioning had contradictory elements of deference to and defiance of power relations that diminished perceptions of novelty in novel activities that mobilized and invoked popular opinion on contentious political issues.